An analysis of high‐resolution modelled wave heights along the South African south coast suggests recent deterioration of sea state. (5th July 2021) - Tara Lyttle, Casey; Rautenbach, Christo; Backeberg, Björn; Jarre, Astrid
Abstract: Understanding climate variability and change together with fishing activities through high‐resolution scientific information and local observations can help implement and sustain improved coastal marine management strategies. Ethnographic data collected between 2010 and 2016 during previous studies with traditional handline fishers on South Africa's south coast suggest that fishers recently observed a deterioration in sea state and a reduction in sea days. Many fishers attributed this deterioration to increased climate variability. The fishers also suggested experiencing increased difficulty when leaving the nearshore through river mouths due to higher waves and stronger winds. The current study investigated these oceanic changes in terms of wave height variability and trends, using high resolution modelled wave data of the south coast for the period 1997–2013. Considering the fishers' perspectives, wave heights near their main launch sites during their main fishing season (austral summer) were focussed on. During the mid‐to‐late 2000s, a positive regime shift of summer nearshore wave heights occurred along the south coast and a statistically significant positive trend in summer nearshore wave heights occurred during the study period. These results support the local fishers' observations suggesting that the sea state had been deteriorating, in terms of higher summer nearshore waves. While the magnitude of the observed change is not critical to small‐boat fisheries in the area at present, it may contribute to the decrease in available sea days and hence, adds to the stressors in the commercial and small‐scale sectors, further increasing their vulnerability to change.